FACTORS PREDICTING COMMUNITY SUPPORT: THE CASE OF A SOUTH AFRICAN ARTS FESTIVAL - I. LOOTS; SURIA ELLIS; ELMARIE SLABBERT (Tourism & Management Studies)
Events are one of the fastest growing tourism attractions in South Africa. This has various implications for the role players involved in hosting the event, especially the community. It is important to obtain the support and loyalty of residents so that potential conflicts can be avoided. However, residents are not always involved in the planning and management of the event, which raises questions about the real benefits they receive. It is therefore the aim of this research to determine the factors predicting community support in the case of a South African arts festival. A survey was done in 2007 at the Klein Karoo National Arts Festival (KKNK), which is one of the largest arts festivals in the country. A stratified random sampling procedure was followed in the community of Oudtshoorn, and 279 questionnaires were completed by residents. Structural equation modelling was done, based on the study of Gursoy and Kendall (2006), to explore the factors and identify its influence on support for the event. It was found that community attachment, costs and benefits perceived were the most important factors predicting community support for the festival, which differs from the results of previous studies. In the case of this study, ecocentric attitudes and issues of community concern did not influence the level of community support the event was given.